O corpo em experiência nas práticas corporais: o Método Self-Healing de Meir Schneider na atenção à saúde - Terra, Janaina Demarchi (2018)
To construct meetings for the production of health and corporal experience having as a mediator the corporal practices was the proposal of this research. The meetings were offered in two areas of Basic Health Care: the Geraldo Horácio de Paula Souza School Health Center, located next to the School of Public Health - USP / SP and the Basic Health Unit José Marcílio Malta Cardoso, both located in the city from Sao Paulo. The research of a qualitative nature counted on the accomplishment of 54 meetings, lasting from an hour and a half to two hours and fifteen minutes, during the period of one year, being one meeting per week. The group meetings were built from a dynamic process, taking into account the demands of the group. For the purpose of proposing bodily experiences, the techniques proposed by Meir Schneider's Self-Healing Method (MSH) were used. Women, mostly elderly, participated in the meetings (although the group was proposed to any interested user). By means of annotations in a field notebook and the recorded speeches by audio recording of the meetings, a letter was organized with the impressions and speeches that stood out throughout the process on the corporal experiences, the care, the reception and the ties built in groups. It was found that these group meetings were fruitful in building the welcoming, of care and the affective bond of the people involved. Meir Schneider's Self-Healing Method has been shown to be an important care and self-care technique in regard to relaxation practices, varied active and passive movements and eye health, demonstrating bringing elements that could add knowledge and bodily experience and, as a consequence, improvement in situations of pain and discomfort. The National Policy on Integrative and Complementary Practices (PNPIC) has legitimized and encouraged new corporal practices in Primary Health Care and the MSH enhanced by group meetings has proved to be a method that can mobilize for new ways of living life with autonomy and care in the measure that it adds the light and light technologies hard in the attention to the health of the populations.